1954
DOI: 10.1111/j.2153-3490.1954.tb01094.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Interpretation of the Diurnal Variation of Cosmic Rays

Abstract: The recorded data of diurnal variation of the cosmic ray intensity are analysed. By using the known deflection of the cosmic ray particles in the geomagnetic field (Brunberg and Dattner 1953) and under an assumption of an anisotropy in the primary cosmic radiation, it is shown that the momentum of the primary radiation and the direction of the anisotropy can be determined. The anisotropy is explained as an effect due to the distribution of cosmic ray particles rotating with the solar magnetic field as suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1954
1954
1964
1964

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is clear from Table 2 that the error committed in assuming 'FE to represent a solar time displacement is quite large. Brunberg and Dattner (1954) have concluded that the mean energy of the primary particles responsible for the daily variation is in the region 2-4 X 10 10 eV. The assumption that lower energies are involved nieets with serious difficulties (cf.…”
Section: '¥E(h)=42° '¥E(m) =29°mentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear from Table 2 that the error committed in assuming 'FE to represent a solar time displacement is quite large. Brunberg and Dattner (1954) have concluded that the mean energy of the primary particles responsible for the daily variation is in the region 2-4 X 10 10 eV. The assumption that lower energies are involved nieets with serious difficulties (cf.…”
Section: '¥E(h)=42° '¥E(m) =29°mentioning
confidence: 99%
“…It does not seem possible to attribute this to uncorrected atmospheric effects, and we discuss below possible sources of this phase difference. Brunberg and Dattner (1954) have suggested that the daily variation arises from an anisotropy of primary particles within the energy range 2-4 X 10 10 eY entering the Earth's field, the direction of the anisotropy lying roughly in the plane of the ecliptic. However, examination of particle trajectories in the field (Brunberg and Dattner 1953) seems to indicate that the anisotropy must involve particles from a wide range of asymptotic latitudes with no strong concentration near the equatorial belt if the observed lack of any marked change in amplitude with latitude is to be explained.…”
Section: (B) Phase Difference In Lmt Between Hobart and Mawsonmentioning
confidence: 99%
See 1 more Smart Citation